Go green for environmental sustainability : an interdisciplinary exploration of theory and applications - Xavier, S. (Savarimuthu), 1970-; Rao, Usha (Geologist); Reynolds, Mark (Mark F.) (CRC Press, Taylor & Francis Group, 2022)
"This book highlights topics ranging from green chemistry and engineering to bioremediation, smart technologies and sustainable business practices. The common threads running through this volume are the need for urgent action, a vision for a sustainable future, and the awareness that solutions must be widely accessible and advance the welfare of all nations, especially in the face of climate change. The authors delineate how we can protect and restore natural ecosystem potential to achieve environmental sustainability. They provide a clear idea of today's environmental challenges and solutions, focus on energy use patterns and the reduction of energy consumption, advocate for increased environmental awareness, and discuss environmental monitoring systems. The book contains many domestic and international case studies and showcases visionary ideas in action to illustrate sustainability principles. This volume provides an in-depth reference for stakeholders from academia, government, and industry on the latest research in environmental sustainability solutions. Compelled by the realization that we do not inherit this Earth from our ancestors but instead borrow it from our children, the authors offer solutions to emergent problems. This research comprises an important contribution to the global effort to build a more sustainable tomorrow"--